An investigation of early memories - Fleminger, Marguerita Estelle (Department of Psychology, 2016)
The object of this investigation was to study certain aspects of childhood recollections. A certain amount of work had been carried out previously on the subject of early memories. There had been investigations designed to determine the average age to which a person's earliest memory dates back, others had been concerned with the sense modalities, affective experiences, and emotions involved in these fragments remembered. In a few studies differences among the subjects themselves had been considered in relation to the memories presented by them. There had been investigations to discover whether differences in race, intelligence, age and sex among the subjects concerned play any part in determining the form and contents of the memories presented by them. In this particular investigation certain aspects of early memories have been studied separately, in relation to one another and in relation to personality differences among the subjects, and an attempt has been made to determine some of the factors which may account for the variance in the type of memories recalled. It should be mentioned that the memories which this investigation was designed to study were not the repressed experiences of early childhood which are recalled with exceeding difficulty, and which are significant for psycho-analytic therapy, but were those memories which might be recalled to consciousness with comparative ease, as will later be seen by the method involved in obtaining them.